Modelling the Effect of Human Body around User on Signal Strength and Accuracy of Indoor Positioning - Firdaus; Ahmad, Noor Azurati; Sahibuddin, Shamsul; Dziyauddin, Rudzidatul Akmam (International Journal of Integrated Engineering, 2020)
WLAN indoor positioning system (IPS) has high accurate of position estimation and minimal cost. However, environmental conditions such as the people presence effect (PPE) greatly influence WLAN signal and it will decrease the accuracy. This research modelled the effect of people around user on signal strength and the accuracy. We have modelled the human body around user effects by proposed a general equation of decrease in RSSI as function of position, distance, and number of people. RSSI decreased from 5 dBm to 1 dBm when people in LOS position, and start from 0.5 dBm to 0.3 dBm when people in NLOS position. The system accuracy decreases due to the presence of people. When the system in NLOS case (Î”RSSI = 0.5 dBm), the presence of people causes a decrease in accuracy from 33% to 57%. Then the accuracy decrease from 273% to 334% in LOS case (Î”RSSI = 5 dBm).